Report of ice and ice movements in Bering Sea and the Arctic basin [electronic resource] - Simpson, Edward, 1860-1930 (Washington : U.S. Hydrographic Office, 1890)
At head of title: N. 92. "Under the direction of Lieutenant Commander Chas. H. Stockton, U.S. N., Commanding U.S.S. 'Thetis'." Electronic reproduction. Mode of access: Internet. 44